Os problemas clássicos da Grécia antiga - Pinto, Luis Paulo [UNESP] (2015)
In ancient Greece, the sages sought to solve problems that were based on geometric construction using only two instruments: non-graduated ruler and compass. Some of these problems have become classics because they require within the development of Mathematics, great efforts to reach a solution. They are: the duplication of the cube, the side of a cube whose volume is twice the volume of a given cube; the trisseção of an angle, which is to divide an angle into three equal parts or three measures angles exactly equal and the squaring of a circle, which consists of constructing a square with the same area as a given circle. In this work we present some geometric constructions with non-graded ruler and compass, some solutions that were not in accordance with the rules laid down and develop the algebraic reasoning which demonstrates the insolubility of the three classic problems cited